EXPERIMENTAL STUDY ON SOME PROTECTIVE METHODS AGAINST HYDATID CYST INFECTION IN MICE - AL- Sultan, I. T.; AL- Kanany, E. R. (The Iraqi Journal of Veterinary Medicine, 2000)
Experimental study albion mice as a host was conducted in on attempt to inactivate the larval stage of Echinococcus granulosus by formalin treatment. Animals were divided into three groups. The first group was inoculated subcutaneously with alive ovine hydatid protoscolices , whereas the second group was inoculated similarly with 0.75% formalin- treated protoscolices. The rhird group was remained as negative control. a comparison was held between the three groups from haematological , immunological and histopathological points of view. The haematological picture revealed lymphopenia, eosinophilia and neutrophilia in both treated groups of mice. Infected mice in groups 1 and 2 responded subcutaneous injection of the antigen by production of antibodies detected by indirect haemagglutination test. Similar responses did not occur in noninfected control mice. Pathologically, results showed that the cellular were concentrated at the site of inoculation and at the draining lymph nodes without spreading to other organs. The formalinized protoscolices failed to induce development or formation of any cysts at the site of inoculation , in comparison with live protoscolices . The challenge of both treated groups at 4 weeks post primary infection showed that 80% of the infected and vaccinated animals resisted infection .